Classification, Biotransformation and Antioxidant Activity of Olive Fruit Biophenols: A Review - Goulas, Vlasios; Gerothanassis, Ioannis P.; Manganaris, George A.; Charisiadis, Pantelis (My University, 2012)
Olive biophenols affect the organoleptic and nutraceutical properties of fruits; therefore, it is an emerging research field. In addition, a plethora of health-promoting properties have been attributed to the phenolic content of olive fruits. The main biophenols can be divided into different sub-groups such as phenolic acids and alcohols, flavonoids, lignans and secoiridoids. The latter sub-group of biophenols is typical in olive fruits, since oleuropein and the products of its biotransformation characterize olive fruit. An array of genetic, agronomic and technological factors that affect the rate of synthesis and biotransformation of secoiridoids in olive fruits is discussed. Furthermore, the relationship between antioxidant activity and structures of olive biophenols is explored
Keywords: Biosynthesis; Agronomy; Fruit; Olive; Plant genetics; Technology; Alcohol